Research on the effect of visceral artery Aneurysm's cardiac morphological variation on hemodynamic situation based on time-resolved CT-scan and computational fluid dynamics. (June 2022) - Gao, Fan; Chen, Bing; Zhou, Tao; Luo, Huan
Highlights: We quantitatively assessed the geometry variation of endovascular cavity which captured by 4D-CTA images. The pulsating characteristics of cavity volume and internal blood vessel wall surface can be observed from morphological parameters. The computational fluid dynamic (CFD) simulation is based on deforming models of aneurysms during cardiac cycle. We quantitatively evaluated the influence of arteries' deformation on simulation results and reproduced the hemodynamic situation during cardiac cycle. Abstract: Background and Objective: Muscular arteries and related aneurysms keep deforming during the cardiac cycle. However, current patient-specific computational fluid dynamics (CFD) analyses of aneurysms are usually based on individual cardiac phase images. The cardiac deformation and displacement characteristics of muscle arteries and aneurysms, as well as their impact on CFD results, have not been adequately explored. The present study tried to illustrate the cardiac morphological variation of visceral muscular arteries (VMAs) & aneurysms (VAAs) and evaluate its influence on the hemodynamic situation at lesion locations. Methods: Four-dimensional computed tomography angiogram (4D-CTA) images of six patients with VAAs were acquired. Medical image registration is used to capture cardiac variations of VMAs. The steady-state CFD simulation is performed on twelve different time-phase geometries. Deformation, displacement, wall shear stress (WSS), velocity, and pressure values at pathological locations are compared to illustrate the deforming characteristics of VAAs and their influence on CFD simulation results. Results: The deformation and displacement characteristics of lesion locations for six specific patients show a pulsatile pattern. Maximum displacements are always less than 4 mm. The ratio fluctuations of endovascular cavity volume and vascular inner wall surface area, which were employed to depict cardiac deformation, are always less than 20%. According to CFD simulations based on deformed VMAs, WSS has a larger coefficient of variation (COV) than velocity and pressure. Except for one patient's WSS, the COVs of different hemodynamic parameters obtained from simulation results are always less than 10%. Conclusions: Based on 4D-CTA images, we confirmed that cardiovascular circulation has a periodic impact on the morphologic characteristics of VMAs. A wave that has extended throughout the studied region is observed. It has a dominant influence on the displacement of VMAs. According to CFD results, the influence of the VMAs' deformation and displacement on different hemodynamic parameters is distinct. The variance in WSS is more prominent compared to pressure and velocity. On most occasions, the influence of the VMAs' periodic deformation and displacement on simulation results is insignificant. However, the variant simulation results induced by deforming VMAs cannot be simply ignored.